Turkish version of the Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration: a preliminary study. - (:unkn) unknown (My University, 2006)
BACKGROUND: The Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration is an established instrument to measure the perceived work relationship between physicians and nurses. The survey addresses areas of autonomy and decision making, interprofessional education and relations, psychosocial care, teamwork, and shared responsibility. The aim of this prelimiary study was to adapt the Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration for use in Turkey and test its psychometric properties and utility in clinical and research practice. METHODS: The process of cross-cultural adaptation and validation followed the guidelines provided in the existing literature. First, three bilingual health professionals independently translated the original questionnaire into Turkish and a consensus version was generated. Then, three other translators, blind to the original questionnaire, performed a back translation into English to confirm the accuracy of the translation. This version was then compared with the original English questionnaire. Discrepancies were discussed and solved by a panel of two nurses and two physicians. The field-testing for face validity was done in a group of ten monolingual physicians and nurses. Reliability was assessed with test-retest reliability and construct validity was confirmed with factor analysis. RESULTS: The mean time of questionnaire administration was 3 minutes and 45 seconds. The test-retest reliability was 0.75, and Cronbach's coefficient alpha was 0.71 for the entire sample. The findings of the factor analysis indicated that the Turkish version of Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration was comprised of the following four factors: 'physician-nurse relationships', 'shared education', 'nursing role in patient care', and 'accountability and responsibility of nurses.' CONCLUSION: The overall findings of this study indicate that the Turkish version of the Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration is a psychometrically sound tool with satisfactory measurement characteristics including construct validity and internal consistency reliability. This instrument may be useful in assessing the effectiveness of educational programs designed to enhance collaboration between physicians and nurses, whether these programs are aimed at residents and graduate nursing students or practicing physicians and nurses.